To be or not to be – a doctor (Res Medica, 2013)
The publication of the first number of Res Medica, the Journal of the Royal Medical Society, is a matter of great interest not only to past, present and future members of the Society, but to all teachers and students in the famous Medical School of Edinburgh. Accordingly, it was both an honour and a privilege to be asked by the Editor to contribute an article which contains a personal message to students and prospective students who may have doubts about the future of the medical profession. It also gives me the opportunity of expressing my best wishes for the success of this journalistic venture.